2021
DOI: 10.3390/biomedicines9080937
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer after Kidney Transplantation: A Screening Colonoscopy Case-Control Study

Abstract: The incidence of colorectal cancer in kidney transplant recipients has been previously reported with conflicting results. In this study, we investigated if the incidence of colorectal advanced neoplasms in kidney transplant recipients, evaluated with screening colonoscopy, was higher than in healthy individuals. One-hundred sixty kidney transplant recipients undergoing screening colonoscopy were compared with 594 age- and sex-matched healthy individuals. Advanced colorectal neoplasia was found in 22 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The latest European Society for Medical Oncology (ESMO) guidelines [ 1 ] describes CRC as the most prevalent cancer in Europe, representing 13.6% of all diagnosed cancers, and being the second cause of mortality with 12.2% of all deaths. Privitera et al [ 6 ] report conflicting evidence on the incidence of CRC in KT patients, which seems to be not significantly different from the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The latest European Society for Medical Oncology (ESMO) guidelines [ 1 ] describes CRC as the most prevalent cancer in Europe, representing 13.6% of all diagnosed cancers, and being the second cause of mortality with 12.2% of all deaths. Privitera et al [ 6 ] report conflicting evidence on the incidence of CRC in KT patients, which seems to be not significantly different from the general population.…”
Section: Discussionmentioning
confidence: 99%
“…This increased cancer risk in the KTR population is driven mainly by de novo cancers, with CRC being the third most common cause of cancer death after non-Hodgkin’s lymphoma and lung cancer[ 8 ]. CRC in KTRs is reported to have a worse 5-year survival rate than in the general population[ 9 , 10 ], and develops more often at a younger age[ 9 - 11 ]. Even so, our patient was diagnosed with an advanced CRC at the age of 36 years.…”
Section: Discussionmentioning
confidence: 99%
“…A cost–benefit ratio is another issue, as it was shown that eight colonoscopies were needed to identify one case of advanced neoplasia in KTRs cohort older than 50 years[ 16 ]. Although some authors suggested that screening colonoscopy in KTRs should be expanded to include recipients younger than 50 years[ 11 ] or even between the age of 35 and 50 years[ 17 ], such a policy would be cost-ineffective, in contrast to a screening program with fecal hemoglobin testing[ 17 ]. However, the latter measure is characterized by poor sensitivity but reasonable specificity.…”
Section: Discussionmentioning
confidence: 99%